A case report: Gliosarcoma associated with a germline heterozygous mutation in MSH2 - Wang, Yuhan; Zhang, Zhiyuan (Frontiers in Neurology, 2024)
Gliosarcoma is a rare subtype of glioblastoma (GBM) with a shorter medical history and a worse prognosis compared to other Grade 4 gliomas. Most gliosarcomas are sporadic, but it is undeniable that a small percentage are linked to germline mutations and several inherited cancer susceptibility syndromes, including Lynch Syndrome (LS). The authors present a case of a primary mismatch repair-deficient gliosarcoma in LS. A 54-year-old Chinese male patient was admitted to the hospital with a history of facial asymmetry for over 1 month and right temporo-occipital pain for 5 days. Head MRI revealed a complex mass lesion in the right frontoparietal region, consisting of cystic and solid components. The patient’s history of colon malignancy and family history of rectal carcinoma were noteworthy. Postoperative pathology indicated the presence of gliosarcoma with high-frequency microsatellite instability (MSI-H) and mismatch repair deficiency (MMRD). Further genetic testing results confirmed a germline heterozygous mutation in MSH2, which is considered the gold standard for diagnosing LS. This case report enriches the existing literature on germline MSH2 mutations and gliosarcomas. It highlights the importance for neurosurgeons to consider possible hereditary disorders when treating patients with a history of concurrent tumors outside the nervous system. Genetic testing is crucial for further identification of such disorders.